Kontribusi Filsafat Ilmu dalam Menentukan Tujuan Pembelajaran Bahasa Arab pada Era Digital - Aufa, Nauwal (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
This study aims to identify the contribution of the philosophy of science in formulating the objectives of Arabic language learning in the digital era, with a focus on the effective use of technology. This research employs a qualitative approach through a literature review integrating the theory of the philosophy of science with contemporary teaching practices. The findings reveal that the ontological dimension of the philosophy of science emphasizes the importance of positioning technology as a means rather than the primary goal of learning. The epistemological dimension directs the use of technology to deepen linguistic competence, maintain scientific integrity, and preserve the connection between learning materials and Islamic values. Meanwhile, the axiological dimension highlights the need to utilize technology to enhance the quality, accessibility, and relevance of learning while fostering students’ character development. The integration of traditional methods—focused on in-depth text comprehension—with digital media-based blended learning models has proven effective in creating interactive, flexible, and philosophically meaningful learning. These findings affirm that the philosophy of science can serve as a strategic guide for educators in designing innovative Arabic language learning that is adaptive to technological advancements yet remains rooted in the values and objectives of Islamic education.